1987
DOI: 10.1002/hep.1840070417
|View full text |Cite
|
Sign up to set email alerts
|

Diminished responsiveness of male homosexual chronic hepatitis B virus carriers with HTLV-III antibodies to recombinant α-interferon

Abstract: In a randomized controlled trial, 41 chronic hepatitis B virus carriers were allocated, by opening numbered computerized randomization envelopes, to receive recombinant interferon-alpha 2A at three different doses: 2.5; 5.0, and 10.0 mU per m2. Thirty-two patients received treatment (6 for 3 months, 26 for 6 months), and 9 patients were controls (received no treatment). Ninety-three per cent of our patients were homosexual, and 41% had anti-HTLV-III in their serum. None of the control patients lost HBeAg. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0
2

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(35 citation statements)
references
References 30 publications
2
31
0
2
Order By: Relevance
“…6,7 Lamivudine, an oral nucleoside analogue, is effective against both HIV and HBV replication. Lamivudine has promptly inhibited HBV replication in more than 80% of cases in both HIV-and non-HIV-infected patients.…”
mentioning
confidence: 99%
“…6,7 Lamivudine, an oral nucleoside analogue, is effective against both HIV and HBV replication. Lamivudine has promptly inhibited HBV replication in more than 80% of cases in both HIV-and non-HIV-infected patients.…”
mentioning
confidence: 99%
“…Several A large multicentre and multinational study has shown that interferon 10 MU three times weekly for three to six months has a greater efficacy than lower doses.3 Our randomised, controlled trial was designed to evaluate the efficacy and safety of high doses of interferon.…”
mentioning
confidence: 99%
“…Based on these considerations we have initiated a pilot study in patients with chronic type B hepatitis with concur rent HIV infection. As chronic type B hepa titis in HIV-infected individuals had a low or no response to IFN-a [3,4] with the excep tion of a recently published study [11], we have attempted to reduce HBV and HIV replication by a combination of AZT and IFN-a. As shown, the combined therapy of IFN-a and AZT, both given in quite low doses, was not able to eliminate the HBV in any of the patients treated.…”
Section: Discussionmentioning
confidence: 99%
“…type B hepatitis frequently becomes chronic [I, 2], Attempts to elimi nate the HBV indicated by the presence of hepatitis B e-antigen (HBeAg) and HBV deoxyribonucleic acid (HBV-DNA) in the serum from the serum of these patients by the use of interferon-a (IFN-a) have not been successful. In fact, these individuals have been shown to be non-or low responders to IFN-a therapy [3,4], Recently, it has been shown that HIV replication can be sup pressed by azidothymidine (AZT). a nucleo side analogue with a high affinity to the reverse transcriptase of the HIV and rather low affinity to eukaryotic DNA polymerases [5].…”
mentioning
confidence: 99%